Hubungan Kecerdasan Interpersonal dengan Interaksi Teman Sebaya Siswa Kelas V SD - Makmur Nurdin; Mujahidah Mujahidah; andifitriani perdana (Jurnal Pendidikan dan Pembelajaran Sekolah Dasar (JPPSD), 2023)
This research is a quantitative research with correlational type which aims to determine the relationship between interpersonal intelligence and peer interaction of fifth grade students of SDN 261 Tarasu. The population in this study were all fifth grade students at SDN 261 Tarasu, totaling 40 students, while the sample was 40 students using non-probability sampling technique. The data analysis technique used is descriptive statistical analysis and inferential statistics. Based on the results of descriptive statistical analysis, the description of interpersonal intelligence is included in the good category and peer interaction is included in the very good category, and the degree of relationship between the two variables is 19.71%. Then based on the results of inferential statistical analysis showed that the tcount 3.0468 is greater than the ttable value of 1.686 at the 5% significance level. Thus H0 is rejected and H1 is accepted. From the results of the study, it was concluded that there was a significant relationship between interpersonal intelligence and peer interaction of fifth grade students at SDN 261 Tarasu, Kajuara District, Bone Regency. © Universitas Negeri Makassar 2023